Evaluating observed and perceived experiences of operating room to paediatric critical care unit handoffs: an initial assessment to inform quality improvement - Davidson, Jacob; Walser, Emily; Waugh, Evelyn V.; Wilson, Claire A.; Strychowsky, Julie; Tijssen, Janice; Biswas, Abhijit; Lam, Jennifer Y. (Frontiers in Pediatrics, 2025)
IntroductionTransferring critically ill patients from the Operating Room (OR) to the Paediatric Critical Care Unit (PCCU) is a complex process. Unstructured handoffs and poor communication increase the risk of adverse events. This project aimed to characterize the current handoff process, identify strengths and deficiencies, and define opportunities for improving patient handover.MethodsA working group with multidisciplinary stakeholder representation was created. An audit tool was developed and used to evaluate daytime OR to PCCU handoffs. A survey was distributed electronically to all staff involved in the handoffs.ResultsAudits of 50 handoffs revealed that only 71.4% of handoffs included the full perioperative team and introductions were rarely completed (14.0%). The majority (81.8%) of the Anaesthesia content was discussed consistently (>60% of the time). In contrast, over half (53.8%) of surgical elements were discussed less than 50% of the time. Sixty-two survey responses revealed team members were often absent (67.0%) or inattentive (45.0%), and handoffs lacked clarification and wrap-up (38.0%). Twenty-two percent of respondents felt information was missed and 60.0% were unsatisfied with the current handoff process. Siloed communication, need for standard pre-handoff information, and a structured handoff process were identified in survey comments.ConclusionAudit and survey data identified multiple areas for process improvements in OR to PCCU handoffs. The combination of objective and subjective data enhanced results and informed future quality improvement efforts by engaging team members. These findings will aid in the development of a structured OR to PCCU handoff process to ensure effective and safe patient care.